From parchment to practice : implementing new constitutions / edited by Tom Ginsburg, Aziz Z. Huq. - Ginsburg, Tom; Huq, Aziz Z. (Comparative constitutional law and policy., 2020)
From Parchment to Practice explores the set of problems that arise when a new constitution has been adopted. All new constitutions must manage a balance or tension between two forces: aspirations for social and political transformation on the one hand and demands for preservation of old interests and institutions on the other. The period following the initial adoption of a new constitution, is the conceptual, temporal, and institutional bridge between the past and future. It is the moment when the transformative and the preservative forces in constitutional design can come into the sharpest conflict. Through a series of case studies, this volume analyzes the variable nature of these type of conflicts - and the diverse means through which they are mediated, whether successfully or not.